O consorcio público intermunicipal como instrumento de gestão dos resíduos sólidos urbanos: um estudo de caso nos municípios de Tucuruí e Breu Branco (estado do Pará) - FONSECA, Devanilda Ranieri Martins da (Universidade Federal do Pará, 2018)
This work aimed to analyze the public intermunicipal trust as a viable instrument from the urban solid waste management in the municipalities of Tucuruí and Breu Branco in the state of Pará, by means of literature review on the topic, analysis of public trusts experiences reported in literature and semistructured interviews with representers from public trusts in Pará and technicians from State Secretariat (SEIR,SEGOV) as well as the application of the sustainability indicators in evaluation of the current urban solid waste management in the cities studied. It was observed, by the proposed methodology, that, despite the difficulties presented in the formation of a public intermunicipal trust in Pará State, such as individualism of public managers, management ability and support (judicial, technical and financial) of the State entity on the implementation of management models associated to the execution of public services of mutual interest, the instrument of public intermunicipal trust seems to be feasible for the urban solid waste management in the cities studied. It can be concluded that the associated management in urban solid waste management allows the minimization of environmental risks and impacts with the optimization of the uses of areas for its final disposal, as well as the gains in production scale with the rationalization of financial, human and technological resources, aiming to increase efficiency in the use of public resources, ability to perform public service of municipalities from Pará in urban solid waste management.